The direction of university radio: a challenge of academic and professional convergence - Ventín Sanchez, José Augusto (2024)
University radio stations in Colombia have become a significant contributor to the country's creative and cultural industry, having developed their unique identities over almost a century of existence. In the last two decades, the number of university radio stations has grown exponentially, with over 80 stations from 60 universities of various types (public and private), identities (confessional, secular, regional, national), and focuses (educational and research). Each station has acquired distinct characteristics. The study presented here used both quantitative (survey and analysis sheets) and qualitative (interview and documentary review) methods to investigate university radio stations and their agents. The aim was to identify and analyze the challenges faced by the directors of this type of radio station. The analysis focused on the relationship between the media and the university, mission objectives, a sustainable content production structure, target audience definition, and event selection reflecting system dynamism. The main conclusion is that university radio is making conceptual progress, but the administrative figure of the director needs strengthening. A manager with strategic skills establishes the tactical direction and oversees the efficient production of high-quality content to effectively communicate with the target audience.